Improving Medical Decision Making and Health Promotion through Culture-Sensitive Health Communication: An Agenda for Science and Practice. (October 2016) - Betsch, Cornelia; Böhm, Robert; Airhihenbuwa, Collins O.; Butler, Robb; Chapman, Gretchen B.; Haase, Niels; Herrmann, Benedikt; Igarashi, Tasuku; Kitayama, Shinobu; Korn, Lars; Nurm, Ülla-Karin; Rohrmann, Bernd; et al.
This review introduces the concept of culture-sensitive health communication. The basic premise is that congruency between the recipient's cultural characteristics and the respective message will increase the communication's effectiveness. Culture-sensitive health communication is therefore defined as the deliberate and evidence-informed adaptation of health communication to the recipients' cultural background in order to increase knowledge and improve preparation for medical decision making and to enhance the persuasiveness of messages in health promotion. To achieve effective health communication in varying cultural contexts, an empirically and theoretically based understanding of culture will be indispensable. We therefore define culture, discuss which evolutionary and structural factors contribute to the development of cultural diversity, and examine how differences are conceptualized as scientific constructs in current models of cultural differences. In addition, we will explicate the implications of cultural differences for psychological theorizing, because common constructs of health behavior theories and decision making, such as attitudes or risk perception, are subject to cultural variation. In terms of communication, we will review both communication strategies and channels that are used to disseminate health messages, and we will discuss the implications of cultural differences for their effectiveness. Finally, we propose an agenda both for science and for practice to advance and apply the evidence base for culture-sensitive health communication. This calls for more interdisciplinary research between science and practice but also between scientific disciplines and between basic and applied research.